SEKTOR BASIS DAN STRUKTUR EKONOMI DI KOTA BANDAR LAMPUNG - Anda Laksmana; Muhammad Irfan Affandi; Umi Kalsum (Lampung University, 2014)
The reasearch that was conducted in Bandar Lampung aims to identify the bases and non-base sectors, identify the economic performance and determine the potential sectors in Bandar Lampung City. This study using quantitative descriptive research model. The data used was Bandar Lampung GDP time series data from 2005 to 2012. It will be analyzed using three analysis tools, namely Location Quotient (LQ), Shift Share (SS) and Growth Ratio Model (MRP). LQ analysis results indicated that there were seven sectors of the base and two sectors of non base. Shift share analysis showed that the performance of the financial sector, leasing and business services have higher growth than other sectors. MRP analysis showed that there were eight potential sector to be developed in Bandar Lampung. Keywords: base sector, economic structure, potential sector